Chewing simulation of zirconia implant supported restorations. Issue 3 (July 2019) - Rohr, Nadja; Balmer, Marc; Müller, Johannes A.; Märtin, Sabrina; Fischer, Jens
Abstract: Purpose: To test three potential prosthetic material options for zirconia implants in regard to their mechanical properties, loading and retention capacity as well as to record abrasion after chewing simulation followed by thermocyclic aging. Methods: Molar crowns (n = 96) of three different computer-aided design/computer-aided manufacturing (CAD/CAM) materials were produced and cemented on zirconia implants (ceramic.implant, Vita) with a diameter of 4.5 mm. Monolithic zirconia (Vita YZ [YZ] with RelyX Unicem 2 Automix [RUN], polymer-infiltrated ceramic (Vita Enamic [VE]) with Vita Adiva F-Cem [VAF] and acrylate polymer (CAD Temp [CT]) with RelyX Ultimate [RUL]. Fracture load and retentive force of the crowns were measured after 24 h water storage at 37 °C and after a chewing simulation followed by thermocyclic aging. Abrasion was recorded by matching stereolithography-data of the crowns obtained before and after chewing simulation. Additionally, the mechanical properties and bonding capabilities of the crown and cement materials were assessed. Results: Fracture load values were significantly highest for YZ > VE = CT. Retention force values did not differ significantly between the materials. The aging procedure did not affect the fracture load values nor the retention force significantly. Abrasion depth of the crowns was lowest for YZ followed by VE and CT. On unpolished crowns, abrasion of YZ and VE tended to be higher than on polished specimens. Conclusions: Based on the obtained in-vitro results, all tested materials can be recommended for the use on zirconia implants, although CT is only approved for temporary crowns. The loading and retention capacity of the materials were not significantly affected by aging.